Study of helminth eggs (Ascaris suum) inactivation by anaerobic digestion and electrochemical treatment [version 2; peer review: 1 approved, 2 approved with reservations] - Srikanth Mutnuri; Prajakta Pratap Patil (Gates Open Research)
Background The use of insufficiently treated wastewater or Faecal sludge in agriculture raises concerns because of the pathogen content. Helminth eggs (HE) are one of the most crucial pathogens for ensuring public health and safety. Widely used disinfection treatment methods do not guarantee the complete inactivation of helminth eggs. The current study evaluated the effectiveness of anaerobic digestion and electrochemical process on helminth (Ascaris suum) egg inactivation. Methods Lab-scale biochemical methane potential (BMP) assay was conducted by spiking A. suum eggs in a serum bottle. Total solid (TS), volatile solid (VS), pH, biogas production and its composition, and volatile fatty acids (VFA) were analyzed along with A. suum inactivation every third day for the initial 15 days and fifth day for 45 days. In the second set of experiments, a hypochlorite (4700 ppm) solution was generated by electrolysis of aqueous NaCl solution in a membrane-less electrochemical cell. The hypochlorite was diluted (940, 470, 235, and 156ppm) in wastewater, spiked with A. suum eggs and then examined for inactivation at regular intervals. Results The results of the anaerobic digestion treatment documented 98% inactivation of A. suum eggs (0.15 eggs/mL) in 35 days and remained at 0.14 eggs/mL until day 45. Correlation analysis revealed a positive relationship between non-viable eggs and pH and a negative relationship with all the other parameters. Electrochemical treatment achieved 10% inactivation at 940 ppm concentration in 24h. Conclusions This study revealed that the inactivation of A. suum eggs by anaerobic digestion or electrochemical treatment is a combined effect of more than one parameter.